Application of Parallel Algebraic Multigrid Algorithms in Geophysics - Rui, Chen; Han-dong, Tan (Procedia engineering, 2012)
With the further development of the electromagnetic exploration technologies, the forward and inversion modeling of geophysical in three-dimensional numerical simulation fields is confronted with huge challenges. During the process of solving the partial differential equations, the methods of finite difference, finite element and volume element methods are usually adopted. For the complex topographic condition and geological structure, the conditions of the matrix formed finally will be very poor, seriously affecting the iterative and convergence rate in equation solution. In this paper, the algebraic multigrid preconditioned methods and conjugate gradient solution process are adopted to conduct parallel processing in combination of graphics processing unit (GPU), and the efficiency of DCs threedimensional forward modeling will be effectively improved.